Facilitative Leadership in the Success of Small-Scale Public Private Partnership Projects: Madiun Street Lighting PPP Project Case Study - Kurniawati, Lestari (Yayasan Sinergi Kawula Muda, 2026)
The success of the Madiun Street lighting PPP as the first small-scale regional PPP project to reach the operational stage is interesting to study. The role of champions in leading and initiating projects is crucial in realizing good governance in infrastructure provision. This study introduces a new perspective on the leadership of the Regent of Madiun as a champion in small-scale PPP projects, which has not been widely researched through empirical studies. This study adopts a qualitative research design, with primary data were obtained through an interview and focus group discussion with multi-stakeholders, and secondary data trough analyzing webinar video related. This research found that in his leadership, the Regent of Madiun built collaboration by empowering all levels and stakeholders involved in the project. Building trust in business entities and stakeholders through open dialogue and discussions in informal forums. Facilitative leadership successfully fastered trust, collaboration, and a sense of ownership among stakeholders.